An evaluation of the utilization of self-help materials in the UP Social Science Library section - Borres, Randy G. (2010)
This study on the evaluation of the utilization of self-help materials in the UP Social Science Library Section aimed to determine what self-help materials in the Social Science section are used by students and to identify the type of self-help materials needed by the Social Science Library section users. Also, the study brought emphasis on the purposes of the students in using self-help materials and their individual topic preferences. The Social Science Library section users from February 22 - March 1 of the 2nd semester AY 2009-2010 were the respondents of the study. One-hundred forty respondents answered the survey and 207 books in the Social Science Reading Room and Social Science Stacks Section were examined. Most of the respondents came from the College of Social Science and Philosophy (CSSP). Majority of the respondents visit the library everyday and once or twice a month and the average hours of visit is 4.26 hours per week.